Social Policy Review 27 : Analysis and Debate in Social Policy, 2015 - Hudson, John; Fenger, Menno; Irving, Zoe (Book collections on Project MUSE., 2015)
This exciting volume brings together international scholarship to address a broad range of issues including the effects of financialisation on services and care provision, policies to address deficiencies in housing and labour markets and ways in which the study of social policy may need to develop.